Examination of Social Appearance Anxiety Levels of University Students - Türkçapar, Ünal (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: The aim of this study is to investigate the social appearance anxiety levels of university students taking physical education course according to various variables. Material and Methods: In the research, descriptive scanning model was used. The study group of this research consists of 929 participants who took compulsory physical education and sports lessons in the preparatory and first year of Kyrgyzstan Turkey Manas University in the 2020-2021 academic year. In order to determine the social appearance anxiety levels of individuals and the "Personal Information Form" prepared by the researcher, the data of the research; The "Social Appearance Anxiety Inventory (SAAI)," developed by Hart et al. (2008) and validated and reliable in Turkish by Doğan (2010) was used. The study was carried out in SPSS 22 statistical package program and the degree of significance was taken as 0.05. Independent-Samples T test was used in pairwise comparisons, and One-Way Anova test was used in multiple comparisons. Results: In the study, no significant difference was found between the social appearance anxiety levels of university students and the variables of gender, class, age, father’s education level and mother’s education level.